Pan-cancer analysis reveals interleukin-17 family members as biomarkers in the prediction for immune checkpoint inhibitor curative effect - Han, Xiaying; Ye, Jianxin; Huang, Runzhi; Li, Yongai; Liu, Jianpeng; Meng, Tong; Song, Dianwen (Frontiers in Immunology, 2022)
Background: The interleukin 17 (IL-17) family contains 6 homologous genes, IL-17A to IL-17F. Growing evidence indicates that dysregulated IL-17 family members act as major pathogenic factors in the early and late stages of cancer development and progression. However, a systematic analysis of the prevalence and predictive value of IL-17 for Immune checkpoint inhibitors (ICIs) therapeutic effectiveness in multiple tumor types remains largely unknown, and the associations between its expression levels and immunotherapy-associated signatures also need to be explored. Methods: The Pan-cancer dataset in The Cancer Genome Altas (TCGA) were downloaded from UCSC Xena (http: //xena.ucsc.edu/). The immunotherapeutic cohorts included IMvigor210, which were obtained from the Gene Expression Omnibus database and included in a previously published study respectively. Other datasets from GEO dataset, PRECOG, GEO and METABRIC databases were also included. In 33 TCGA tumor types, the pan-cancer analysis was carried out including their expression map, clinical risk assessment, immune subtype analysis, along with their association with the stemness indices, tumor microenvironment (TME) in Pan-Cancer, immune infiltration analysis, ICIs-related immune indicators and drug sensitivity. RT-PCR was also carried out to verify the gene expression levels among MCF-10A and MCF-7 cell lines. Results: The expression of IL-17 family is different between tumor and normal tissue in most cancers and consistency has been observed between gene activity and gene expression. The result of RT-PCR shows that the expression differences of IL-17 family of human cell (MCF-10A and MCF-7) are consistent with the bioinformatics differential expression analysis. Besides, the expression of IL-17 family can be a sign of patients’ survival prognosis in some tumors and varies in different immune subtypes. Moreover, the expression of IL-17 family presents a robust correlation with immune cell infiltration, ICIs-related immune indicators and drug sensitivity. High expression of IL-17 family is significantly related to immune-relevant pathways. And the low expression of IL-17B means a better immunotherapeutic response in BLCA. Conclusion: Collectively, IL-17 family members may act as biomarkers in predicting the prognosis of the tumor and the therapeutic effects of ICIs, which provides new guidance for cancer treatment.